2014
DOI: 10.1021/la5004935
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Adsorption Layer of Silver Nanoparticles in Sodium Bis(2-ethylhexyl) Sulfosuccinate Solutions in n-Decane As Observed by Photon-Correlation Spectroscopy and Nonaqueous Electrophoresis

Abstract: Photon correlation spectroscopy, nonaqueous electrophoresis, and transmission electron microscopy were used to study the structure of silver nanoparticles (NPs) in n-decane, as a dependence of the concentration of sodium bis(2-ethylhexyl) sulfosuccinate (AOT) and temperature. If the concentration of AOT is lower than the critical micelle concentration (CMC), a silver NP is covered with a monolayer of AOT and reveals no electrophoretic mobility. At average concentrations (from CMC to 0.1 M) the hydrodynamic dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Many studies showed that micelles can be adsorbed on the surface of NPs, thus forming a developed adsorption layer. 20,33 As a result, PCS gives strongly overestimated diameters, which are the sum of the particle diameter and a double thickness of the adsorption layer of micelles. To get a true value of the particle diameter, the obtained dispersion should be diluted to surfactant concentrations lower than the critical micelle concentration (CMC is commonly equal to 10 −4 −10 −3 M).…”
mentioning
confidence: 99%
“…Many studies showed that micelles can be adsorbed on the surface of NPs, thus forming a developed adsorption layer. 20,33 As a result, PCS gives strongly overestimated diameters, which are the sum of the particle diameter and a double thickness of the adsorption layer of micelles. To get a true value of the particle diameter, the obtained dispersion should be diluted to surfactant concentrations lower than the critical micelle concentration (CMC is commonly equal to 10 −4 −10 −3 M).…”
mentioning
confidence: 99%